Knowledge and Attitudes of Oral Health Professionals to Different Dental Treatment Approaches in Bisphosphonate Therapy - Şebnem Dirikan İpci; Gökser Çakar; Cavid Ahmedbeyli; İlknur Özenci; Yasemin Dedeoğlu (Current Research in Dental Sciences)
Objective: This study evaluates oral healthcare professionals’ attitudes towards managing different dental clinical scenarios considering different durations and administration routes of antiresorptive drugs. Methods: This study is a cross-sectional, Web-based survey. The first part of the survey evaluated demographic data; the second part investigated dentists’ medication-related osteonecrosis of the jaw (MRONJ) treatment approach; the third part comprised clinical treatment scenario questions regarding the administration route and duration of usage. Oneway ANOVA test was used in the intergroup comparison of parameters showing normal distribution, and Tamhane's T2 test was used to determine the group that caused the difference. Student t-test was used for comparison of parameters showing normal distribution. The chi-square test, Continuity (yates) correction, and Fisher Freeman Halton test were used to evaluate qualitative data. Significance was set at P